The Influence of Monocular Spatial Cues on Vergence Eye Movements in Monocular and Binocular Viewing of 3-D and 2-D Stimuli. (August 2015) - Batvinionak, Anton A.; Gracheva, Maria A.; Bolshakov, Andrey S.; Rozhkova, Galina I.
The influence of monocular spatial cues on the vergence eye movements was studied in two series of experiments: (I) the subjects were viewing a 3-D video and also its 2-D version—binocularly and monocularly; and (II) in binocular and monocular viewing conditions, the subjects were presented with stationary 2-D stimuli containing or not containing some monocular indications of spatial arrangement. The results of the series (I) showed that, in binocular viewing conditions, the vergence eye movements were only present in the case of 3-D but not 2-D video, while in the course of monocular viewing of 2-D video, some regular vergence eye movements could be revealed, suggesting that the occluded eye position could be influenced by the spatial organization of the scene reconstructed on the basis of the monocular depth information provided by the viewing eye. The data obtained in series (II), in general, seem to support this hypothesis.